Рациональные температуры при шлифовании некоторых наплавленных и напыленных на рабочие поверхности деталей сталей, сплавов и химических соединений (часть 2) - Лебедев, В. Г.; Клименко, Н. Н.; Чумаченко, Т. В. (НТУ "ХПИ", 2014)
Рассмотрены закономерности изменения фазово-структурного состояния наплавленного или напыленного слоя на рабочих поверхностях деталей машин в зависимости от температуры шлифования. Показано, что температура шлифования может оказывать негативное влияние на надежность и долговечность однофазных сталей и сплавов, не испытывающих фазовые превращения. Даны рекомендации по выбору безопасного температурного режима при различных видах шлифования

The article considers the changes in patterns of phase-structural state of the deposited or sprayed layer on the working surfaces of machine parts, depending on the temperature grinding. It is shown that the temperature of grinding can have a negative impact on the reliability and durability of single-phase steels and alloys that do not undergo phase transformations. Recommendations were made for choosing a safe temperature control in various types of grinding. It is also shown that when grinding non ferrous alloys, especially titanium, temperature of mechanical treatment should be strictly seasoned, not to obtain thermal defects on grinding surface
Rational temperature when grinding some overlaid and deposited on the working surfaces of parts of machins of steels, alloys and chemical compounds
Keywords: наплавленный слой; напыленный слой; процесс наплавки; заготовка; deposited layer; sprayed layer; temperature of grinding; rational temperature